Fast self-healing in a layered molecular crystal mediated by stress-induced symmetry breaking - Ghosh, Ishita; Biswas, Rabindra; Tanwar, Manushree; Bhunia, Surojit; Das, Kaustav; Torris, Arun; Mondal, Amit; Raghunathan, Varun; Kumar, Rajesh; Reddy, C. Malla (Nature Communications, 2026)
In recent years, symmetry-breaking has emerged as a powerful tool for significantly altering various physical properties in 2D layered materials. However, the breaking of symmetry by means of mechanical stress in organic crystals remains elusive. Here, we demonstrate a simple approach to engineer symmetry-breaking through mechanical stress fields in a layered molecular crystal, resulting in autonomous and fast self-healing under ambient temperature and pressure conditions. Fracture mechanics analysis reveals that the crystal adheres to an elasto-plastic model, with formation of a plastic zone at the crack tip, which prevents further crack propagation, facilitating the self-healing process. Spatially resolved Raman mapping reveals that the crack formation is accompanied by a distinct symmetry-breaking mechanism at the microstructural level. A six-fold increase in non-linear second harmonic (SH) activity, triggered by mechanical perturbation, further validates the local symmetry breaking in an otherwise centrosymmetric crystal. Furthermore, symmetry is restored following successful healing, as evidenced by the disappearance of the SH signal in the healed regions. This study not only broadens the scope of self-healing mechanisms viable in molecular materials but also offers key insights into the role of symmetry breaking and its potential for related technological applications.